[PP.26.02] PROGNOSTIC VALUE OF VISIT-TO-VISIT VARIABILITY IN SYSTOLIC BLOOD PRESSURE ON CARDIOVASCULAR EVENTS IN HYPERTENSIVE PATIENTS: 30 MONTHS FOLLOW UP. (September 2017) - Ilic, M. Deljanin; Stojanovic, S.; Ilic, S.; Petrovic, D.; Ilic, B.
Abstract : Objective: To investigate the association between visit-to-visit variability in systolic blood pressure (SBPV) and development of cardiovascular events: angina pectoris (AP), myocardial infarction (MI), stroke and cardiovascular death in hypertensive patients (pts), and to estimate whether SBPV could be prognostic marker for cardiovascular events. Design and method: 300 hypertensive pts (148 men, mean age 67.7 ± 9.8 y) were studied. The study comprised three visits during the follow up period of 30 months. SBPV for each patient was defined using the standard deviation from 3 values of systolic BP (SBP-SD). In order to estimate distribution SBPV, quartiles of SBP-SD were introduced. High SBPV were defined as SBP-SD above the 4th and 3rd quartile. Results: During 30 months follow up, in 60 (23%) pts cardiovascular events were occurred: MI 10 (3%), AP 45 (15%), stroke 5 (2%) while cardiovascular death was not observed. The mean SBP-SD during follow up was 11.49 ± 9.24 mmHg and it was significantly lower at each following visit (16.20 ± 13.34 vs 9.91 ± 6.80 vs 7.11 ± 3.72, respectively, p < 0.01). The first quartile included SD values < 6.00 mmHg, the 2nd between 6.01–10.00 mmHg, the 3rd between 10.01–16.99 mmHg, and the 4th quartile values >17.00 mmHg. Univariate analysis showed that there was a significant relationship between SBP-SD and cardiovascular events (OR = 1.115; 95% CI 1.071–1.163, p < 0.001). Non-adjusted OR showed that the highest variability of blood pressure was recorded in the 3rd and 4th quartile (OR = 1.312, 95% CI 1.135–2.042, p < 0.001). A cut-off value of SBP-SD = 12.24 mmHg predicted the cardiovascular events with a sensitivity of 66% and specificity of 65%, while value of SBP-SD < 12.24 mmHg was associated with lower risk for cardiovascular events. During 30 months follow up, the highest variability of blood pressure was recorded in the 3rd and 4th quartile in patients who had stroke, than in patients who had MI, and the lowest in patients with AP (4th quartiles: 47.38 ± 8.03; 43.54 ± 7.66; 32.67 ± 8.55; p < 0.001; 3rd quartiles: 27.13 ± 6.64; 26.42 ± 8.46; 21.648 ± 1.81 respectively, p < 0.01). Conclusions: Our results showed an association between increased SBPV and development of cardiovascular events in hypertensive pts. Value of SBP-SD>12.24 mmHg may be a useful prognostic marker for future cardiovascular events.